The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00414-017-1677-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of 12 X-STR loci in the Serbian population from Vojvodina Province

Abstract: The analysis of 12 X-STR loci included in the Investigator® Argus X-12 kit was performed on a sample of 325 unrelated persons from Vojvodina Province, Republic of Serbia. No significant differences were observed in the allele frequencies in males and females. Heterozygosity values among the studied loci ranged from 67.62 to 94.28%. All loci in female individuals were consistent with the Hardy-Weinberg equilibrium test. The combined power of discrimination values in male and female individuals was 0.9999999994 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Short tandem repeats (STRs) or microsatellites, are present in noncoding intron regions of the human genome and are extensively used for forensic identifications in forensic DNA laboratories all over the world [12][13][14][15][16][17]. STRs usually comprise of tandem repeat motif from 2-6 base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Short tandem repeats (STRs) or microsatellites, are present in noncoding intron regions of the human genome and are extensively used for forensic identifications in forensic DNA laboratories all over the world [12][13][14][15][16][17]. STRs usually comprise of tandem repeat motif from 2-6 base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering all aforementioned, knowledge about mutation rates and possible mutational processes of different STR loci is important for accurate genetic profiles interpretation (Qian et al, 2015;Hamester et al, 2019). As previously mentioned in the Introduction section, a number of population-genetic studies, focused on evaluating of forensic efficiency parameters of STR markers (Grskovic et al, 2013 2016; Crnjac et al, 2017;Veselinovic et al, 2018;Al-Eitan et al, 2019;Al-Eitan et al, 2020;Pilav et al, 2020;Takic Miladinov et al, 2020) indicated a high degree of reliability of these markers important for all kinds of forensic-genetic analyses, including kinship and parentage testing. Finally, results from these two cases clearly demonstrate that X-STR markers have the potential to solve parentage cases not easily solved by standard analysis based on autosomal STR markers.…”
Section: Discussionmentioning
confidence: 99%
“…Besides high heterozygosity, discriminating power, clearly defined repetitive units and precisely determined allelic variants, simple amplification and detection of STR markers make them ideal for forensic analyses (Khalil et al, 2008;Primorac et al, 2014;Gomes et al, 2020). STR markers located on the autosomal, X and Y chromosomes are highly informative, practical and reliable for all kinds of forensic-genetic analyses including parentage testing, what was strongly supported by many population-genetic studies focused on investigating allele frequencies and forensic parameters (such as heterozygosity, power of discrimination, power of exclusion, polymorphic information content, matching probability and typical paternity index) of autosomal STR (Al-Eitan and Tubaishat, 2016;Al-Eitan et al, 2019;Al-Eitan et al, 2020;Pilav et al, 2020;Takic Miladinov et al, 2020) and X-STR loci (Grskovic et al, 2013;Crnjac et al, 2017;Veselinovic et al, 2018) in different populations. Generally, parentage testing follows Mendelian inheritance law, according to which child receives one allele from the mother and the other allele from the father .…”
Section: Introductionmentioning
confidence: 94%
“…We refer to these data as our primary data set. Additional publications [14][15][16][17][18][19][20][21][22][23][24][25] listed in Supplementary Table 1, with only cluster specific haplotypes were considered for a subset of the analyzes. We refer to these data as our secondary data set.…”
Section: Datamentioning
confidence: 99%